Abstinence duration and psychopathology among addiction outpatients during 18 months of COVID-19 - Daigre, Constanza; Palma-Álvarez, Raul Felipe; Sorribes-Puertas, Marta; Ortega-Hernández, German; Perea-Ortueta, Marta; Ros-Cucurull, Elena; Segura, Lidia; Colom, Joan; Braquehais, Maria Dolores; Ramos-Quiroga, Josep Antoni; Grau-López, Lara (Frontiers in Psychiatry, 2024)
The COVID-19 pandemic has impacted the mental health of patients with substance use disorder (SUD). However, few longitudinal studies have been done which examine associations between the pandemic, SUD patients' mental health and their drug use.Objectives: This study aimed to examine duration of abstinence according to psychiatric status among SUD outpatients followed-up for 18 months from the pandemic related lockdown.A follow-up study of 316 SUD outpatients was undertaken. Sociodemographic features, and clinical and consumption related variables were recorded. Pre, during and post lockdown information was evaluated. Abstinence/substance use was monitored at the patient's scheduled follow-up appointments, and psychiatric disorders and psychological variables were revaluated at 18 months.Results: Survival analyses were used to compare the duration of abstinence (in months) from the beginning of the lockdown. It was observed that 70% of patients consumed the main substance for which they were being treated at some point during the follow-up. Men, younger patients, those with more symptoms of anxiety and personality disorders, and patients who experienced increased craving during follow-up, showed shorter duration of abstinence. While patients who had previously maintained at least one year of abstinence, achieved better results.During the first year and a half of the pandemic, SUD outpatients presented alterations in mental health, such us anxiety, depression and maladaptive personality traits and a high rate of relapse. For this reason, despite the health and social crisis and their restrictive measures, a comprehensive treatment should be ensured.